Double Dividends and Mixed Blessings: Structural Transformation, Income Inequality and Employment Dynamics. Issue 9 (1st September 2020) - Sen, Kunal; Sumner, Andy; Yusuf, Arief
Abstract: This paper provides an introduction to a special section on structural transformation, income inequality and employment dynamics. The set of papers in the special section in different ways revisit the seminal works of Lewis, Kuznets and Kaldor in a contemporary context.